Eksplorasi Teknik Shibori dan Sashiko pada Kebaya - Amaranggana, Ayoedya; Wahyuningsih, Sri Endah (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2024)
Abstract. Kebaya is widely worn by all kinds of people to attend certain occasions. The prestige of kebaya today has made a lot of progress on several kebaya models that make a lot of Indonesian designers compete – a competition to create new interesting innovations. Kebaya, which has been found in the community so far, has no one innovated Kebaya by combining shibori techniques and sashiko techniques in their manufacture. The purpose of this study is to determine the results of the exploration of shibori and sashiko techniques on kebaya. This research is a Research and Development (R&D) research using the ADDIE development model which is simplified into four stages which include: (1) analysis, (2) design, (3) development, (4) implementation. Data collection using product observation sheet questionnaire by Expert Judgment, Data analysis technique using percentage descriptive analysis technique. The results of the study, Kebaya A made from linen using the kanoko shibori technique and the Shippo-Tsunagi pattern got an average overall percentage of 80.73% slightly higher than the kebaya B made from mori primissima using the itajime shibori technique and the Seigaiha pattern produced a percentage of 80.21%. This study concludes that the assessment results of the three expert panelists have an average overall percentage of 80.47% with very high criteria. The suggestion for this study is that in the next study, you can use natural dyes because this study still uses commercial synthetic dyes that are not good for the environment. Keywords: Shibori, Sashiko, Kebaya Abstrak. Kebaya banyak dikenakan oleh semua kalangan untuk menghadiri acara-acara tertentu. Pamor kebaya pada jaman sekarang banyak mengalami kemajuan pada beberapa model kebaya yang membuat para desainer indonesia berlomba – lomba menciptakan inovasi baru yang menarik. Kebaya yang dijumpai di masyarakat sejauh ini, belum ada yang melakukan inovasi dengan menggabungkan teknik shibori dan teknik sashiko pada pembuatannya. Tujuan dari penelitian ini yaitu untuk mengetahui hasil eksplorasi teknik shibori dan sashiko pada kebaya.Penelitian ini merupakan penelitian Research and Development (R&D) menggunakan model pengembangan ADDIE yang disederhanakan menjadi empat tahapan yang meliputi : (1) analisis, (2) desain, (3) pengembangan, (4) implementasi. Pengumpulan data menggunakan Angket lembar observasi pengamatan produk oleh Expert Jugdment, Teknik analisis data menggunakan teknik analisis deskriptif persentase. Hasil Penelitian, Kebaya A berbahan linen menggunakan teknik kanoko shibori dan pola Shippo-Tsunagi mendapatkan rata-rata persentase keseluruhan 80,73% sedikit lebih tinggi dari pada kebaya B berbahan mori primissima menggunakan teknik itajime shibori dan pola Seigaiha menghasilkan persentase 80,21%. Simpulan dari penelitian ini yaitu hasil penilaian dari tiga panelis ahli memiliki hasil rata – rata persentase keseluruhan sebesar 80,47% dengan kriteria sangat tinggi. Saran untuk penelitian ini yaitu pada penelitian selanjutnya dapat menggunakan pewarna yang alami dikarenakan penelitian ini masih menggunakan pewarna sintetis komersial yang kurang baik untuk lingkungan. Kata Kunci : Shibori, Sashiko, Kebaya